A review of the development and application of soybean‐based diets for Pacific white shrimp Litopenaeus vannamei. (5th July 2013) - Sookying, D.; Davis, D.A.; Soller Dias da Silva, F.
Abstract: The production of the Pacific white shrimp ( Litopenaeus vannamei ) has expanded to the point of being the most widely cultured species of shrimp. One of the advantages of this species is its acceptance of a wide variety of feed formulations including plant‐based feeds. Given the increases in ingredient costs, particularly fish meal, there is considerable interest in the use of alternative feed formulations for cultured species. Given that soybean meal is one of the most widely available protein sources for which production can be expanded, the move to soy‐based diets is inevitable. The successful use of alternative feed ingredients for shrimp production depends on a number of factors. This paper summarizes studies regarding the move towards high soy diets concerning manipulation of ingredients and nutrient profiles to maintain balanced feed formulations.